Osce for medical students: radiology book 1 - Abd Aziz, Azian; Md Ralib@Md Raghib, Ahmad Razali; Hassan, Radhiana; Che Mohamed, Siti Kamariah; Abdul Rahim, Mohamad Shahrir; Abidin, Mohd Radhwan (Nazdee Resources, 2021)
This ebook contains compilation of OSCE questions prepared for undergraduate MBBS examinations as part of assessment after Radiology posting.